Dignity for deeply forgetful people : how caregivers can meet the challenges of Alzheimer's disease - Post, Stephen Garrard, 1951- (Johns Hopkins University Press, 2022)
"A new ethics guideline for caregivers of "deeply forgetful people" and a program on how to communicate and connect based on 30 years of community dialogues through Alzheimer's organizations across the globe"--